IMPACT OF CYBER-ATTACKS ON BANKING INSTITUTIONS IN INDIA: A STUDY OF SAFETY MECHANISMS AND PREVENTIVE MEASURES - Suman Acharya , Sujata Joshi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research paper aims at studying the catastrophic impact of cybercrime on banking institutions, cyber security measures attempted to curb its effect and development of a robust cyber security mechanism. In recent years banks are its direct victim. In India, a number of banks generally fall prey to the massive malware attacks; it not only leaks valuable and sensitive information but also causes heavy financial losses. The objective of this study is to identify the business areas which are more susceptible to cyberattacks and to ensure customization and development of cyber security protocol. The study involves secondary data analysis from various web resources such as government websites, articles, and research papers available; it also includes case study analysis of different cyber threats and crimes that caused huge financial loss in the past. This paper will provide insights on cyber regime which will benefit banks, financial institutions, and society at large